Approaching the 21st century : - Okita, Saburo (Japan Times, 1990)
While Japan has been allying constantly with the United States during the Cold War, new conditions in a multi-polar world since the early 1990s and new threat perceptions namely due to the awareness of the phenomenon called global terrorism have shaped Japans security perceptions. Based on the dichotomous approach of fear of abandonment fear of entrapment, this article seeks to clarify the motivations for Japan strengthening its alliance with the US after 2001 to counter-balance emerging threats in East Asia.